Erosion behavior of nickel diffusion membranes in conditions of water electrolysis - Glazunov, G.P.; Bodnar, A.S.; Konotopskiy, A.L.; Vinogradov, D.M.; Maznichenko, S.M.; Garkusha, I.E. (Problems of Atomic Science and Technology, 2022)
Preliminary studies of the erosion resistance of Ni diffusion membranes under the conditions of water electrolysis in various modes were carried out. Particular attention was paid to the time dependencies of the current, voltage and the electrolyte temperature during the process. Both electrodes, anode and cathode, were in the form of tubes of Ni-99.5% wt. The electrolyte was pure drinking water after the filter with mineralization (ppm) 14, as well as water with the addition of sodium bicarbonate (mineralization 140...160 ppm). It is demonstrated that after several hours of operation cathodes showed no signs of erosion or other damages. The degree of erosion was assessed by weighing, and the state (morphology) of the surface was visually examined using an optical microscope. As for the anode, even when electrolyzing sufficiently pure water (ppm = 14), there is noticeable erosion and surface damage. To elucidate the reasons for such behavior of Ni electrodes, further studies are planned, in particular, using some other materials as an anode.